Analisis Metode Agile Framework dalam Pengembangan Sistem Informasi Kelurahan Plaju Darat - Putra, Bayu Wijaya; Saputra, Ariansyah; Sanjaya, M. Rudi (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
Data management at the village level still faces various obstacles, especially in recording and utilizing information related to regional potential, such as economic, social, and infrastructure aspects. The diversity of data documentation hinders the analysis process and decision-making by the Village Head based on accurate data. There are weaknesses in data and document access, resulting in inefficiency in searching, updating, and validating data. The development of information systems at the village level is an important step in improving the efficiency of public services and administrative transparency. This study aims to apply the Agile Framework, especially the Scrum method, in the development of the Plaju Darat Village Information System, Palembang City. The system developed is designed to manage population data, regional potential, and administrative services more efficiently and responsively. This research method uses a qualitative approach with this research design, which involves a system development process through five sprints over five weeks. The results of the study show that the application of the scrum method allows the creation of more flexible and iterative applications so that they can quickly adapt to the needs of government administration. The evaluation of the system usability assessment using SUS (System Usability Scale) achieved a score of 81.06% where the system developed using the agile method has been able to provide optimal results not only in terms of good application development in a short time, but also in terms of usability that has been well received by users.